Learning Development of Tahfizh Al-Qur’an Based on Character Building Through Multimedia Autoplay in Class VIII SMP IT Darul Hasan Padangsidimpuan - Ihsan Siregar; Thofik Hidayat; Rina Juliana (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2020)
The emergence of the paradigm that religious learning is not a graduation standard affects the learning of tahfizh al-Quran. So that teachers are required to be able to attract interest in tahfizh al-Qur'an at SMP IT Darul Hasan Padangsidimpuan. The use of multimedia is an option in arousing interest in learning. Burner and Edgar Dale stated that the use of interactive learning media will increase enthusiasm for learning and make it easier for students to understand learning material. Multimedia autoplay which integrates sound, images, video and text media is expected to help. the effectiveness of the process of learning tahfizh al-Qur'an. This study aims to develop learning tahfizh al-Quran based character building through multimedia autoplay in class of VIII SMP IT Darul Hasan Padangsidimpuan, because teaching and learning activities (KBM) use multi method and multimedia, but limited to the use of print media so that it seems less effective. This study also uses the method of development (research and development). Development of instructional media based on Multimedia-based Instructional Design model ADDIE (Assessment/Analysis, Design, Development, Implementation and Evaluation). The aim is to design effective and systematic learning. Media development through the situation analysis stage, media development and media creation, through design trials and subject trials. Types of qualitative and quantitative data. The data collection instrument used a trumpet and a test. Data analysis through descriptive and test data analysis. As many as 32 respondents had pre-test and post-test scores, deviation freedom 30, sig.2 tailled 0.000 with 95% confidence degree, while the pre-test mean score was 68.96, and post-test mean score was 82.90. The lowest score was pre-test 54, the highest was 82, the lowest score was 70 and the highest was 90. Based on these results, the student's score increased by 12.94 points or 18.49%